Trim Tabs investing : using liquidity theory to beat the stock market - Biderman, Charles, 1946- (Wiley, 2005)
Whether you are an investment professional managing billions of dollars or an individual investor with a small nest egg, TrimTabs Investing shows you how to beat the major stock market averages with less risk. This groundbreaking book begins by comparing the stock market to a casino in which the house (public companies and the insiders who run them) buys and sells shares with the players (institutional and individual investors). TrimTabs Investing argues that stock prices are primarily a function of liquidity - the amount of shares available for purchase and the amount of money available to buy them - rather than fundamental value. Finally, it outlines the building blocks of liquidity theory and explains how you can use them to predict the direction of the stock market." Charles Biderman, a savvy and battle-scarred veteran of the investment wars, has fashioned an intriguing approach to making money in the stock market that adroitly avoids both heavy - breathing speculation and the standard Wall Street practices that enable investors, big and small, to lose money in good markets as well as bad. Aimed at the sophisticated investor (which may or may not be an oxymoron), the book is written in blessedly straightforward prose and is a worthwhile read for anyone with an urge to have a fling at investing. -- Alan AbelsonBarron's "Since the days of Joseph and Pharaoh, it has been axiomatic that the size of the grain harvest affects the level of grain prices; but today's investors have been slow to appreciate the fact that the supply of stock shares significantly determines the level of stock prices. Biderman's long overdue book outlines the theory and evidence behind 'Trading Float, ' the actual - and exploitable - power behind major moves in the stock market. -- Paul Montgomery, CEO and CIO of Montgomery Capital Management"' Trade as corporate execs do, not as they say.' Charles Biderman has built an impressive list of hedge fund clients from this essential insight, and this book does a great job explaining exactly how retail investors can incorporate it into their investing."--Eric Zitzewitz, Assistant Professor of Economics, Stanford Graduate School of Business "Charles Biderman is a smart thinker, clear writer - and he offers here some very interesting ideas. This book is for the little guy who enjoys reading about money and economics, even if he doesn't adopt the strategies offered here; and for the professional or sophisticated investor, who, to a greater or lesser degree, just might. -- Andrew Tobias, author of The Only Investment Guide You'll Ever Need